PENGARUH BAHAN AJAR ICT FISIKA MENGINTEGRASIKAN MSTBK TOPIK GERAK, GRAVITASI, DAN ENERGI TERHADAP KOMPETENSI FISIKA SISWA KELAS XI SMAN 1 PADANG - Fadhila Ulfa Jhora; Akmam Akmam; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2015)
Learning material by integrating competency in learning process is important. In fact integration of competency in learning material does not conducted yet. An alternative solution to solve this problem was to apply the ICT learning material by integrating Mathematics, Science, technology, disaster, and character values (MSTDC). The purpose of this research were to determine the competency of the Physics students and to investigate the effect ICT learning material by integrating MSTDC to the competency of Physics students grade XI  at SMAN 1 Padang. Type of research was quasi experimental research with randomized control group only design. The population in this research were the students grade XI MIA SMAN I Padang who were registered in the 2014/2015 academic year. Sampling technique was purposive sampling. There were three instruments in this research, tose are test sheet of knowledge domain, observation sheet of attitude domain, and performance sheet of skill domain. Based on the data analysis could be presented the result of this research. First, the average value of students which use ICT learning material of Physics by integrating MSTDC in knowledge domain, attitude domain, and skill domain respectively 87.52, 90.52, and 86.90. Second, the use of ICT learning material by integrating MSTDC has given significant effect toward Physics competency of students grade XI  SMAN 1 Padang at 0,05 signifacation lev